STRATEGI PENGEMBANGAN USAHA PENGGEMUKAN DAN PEMOTONGAN DOMBA DI TRIAKSA FARM, YOGYAKARTA - Al-Ahmad, Qodrat Nasho Ihul Ibad; Ramadhan, Ayat Adi Putra; Anaji, M Farhan; Maswadi, Maswadi; Liw, Sohibul; Winasih, Wahyu Rahma; Sukoco, M Altaf Syarif; Dewi, Meita Puspa (Agros Journal of Agriculture Science, 2024)
The sheep fattening and slaughtering business has quite high prospects in the Special Region of Yogyakarta because many restaurants use lamb as the main raw material. This study aims to analyze the development of Triaksa Farm sheep farming and develop a strategy for developing livestock farming businesses. This research was conducted at Triaksa Farm located in Margomulyo, Seyegan, Sleman, Yogyakarta, on May 13, 2024. The method used in this study is qualitative, using interview techniques. The data obtained were analyzed using SWOT analysis techniques. The results of the analysis show that Triaksa Farm sheep farming has the potential to be developed. However, several things must be considered, namely improving the quality of sheep production and collaborating with the government to improve the quality of human resources through organizing socialization, training, and motivating Triaksa Farm workers so that they can produce quality sheep and find better ways to maintain sheep.